2017
DOI: 10.1039/c6nr07532k
|View full text |Cite
|
Sign up to set email alerts
|

CDC20siRNA and paclitaxel co-loaded nanometric liposomes of a nipecotic acid-derived cationic amphiphile inhibit xenografted neuroblastoma

Abstract: Despite significant recent progress in the area of translational genomics of neuroblastoma, the overall survival rates for children with high-risk NB continue to be not more than 5 years due to tumor relapse and/or drug-resistant tumors. Herein we report on the development of a neuroblastoma targeting nanometric (130-150 nm) circulation stable liposomal system prepared from a novel nipecotic acid-derived cationic amphiphile (NACA). The size ranges of liposomes (130-150 nm) were confirmed by both dynamic light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…These results are in agreement with the findings of our studies reported here 18. Bhunia and colleagues, exhibited the synergistic effect of CDC20siRNA and paclitaxel, employing nanometric liposomes, which inhibited xenografted neuroblastoma 25. The synergistic effects of QC and DOX on the gene expression of CDC20 have not been fully elucidated on the gastric cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with the findings of our studies reported here 18. Bhunia and colleagues, exhibited the synergistic effect of CDC20siRNA and paclitaxel, employing nanometric liposomes, which inhibited xenografted neuroblastoma 25. The synergistic effects of QC and DOX on the gene expression of CDC20 have not been fully elucidated on the gastric cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…3–7 Recent years, nanomedicine has emerged as an innovative and promising strategy for more effective and safer cancer treatment. 8–11 Tremendous attention has been paid to develop various kinds of nanoscale drug delivery systems (nDDS), such as liposomes, 12–15 dendrimers, 16–18 micelles, 19–23 inorganic nanomaterials, 24–30 and so on. Two main approaches have been employed to prepare nanoformulations of anticancer drugs, including directly encapsulating drugs with nanocarriers and conjugating drugs to macromolecular nanovectors.…”
Section: Introductionmentioning
confidence: 99%
“…The stable circulation of this liposomal system, which is delivered by intravenous administration enhances the therapeutic efficacy with experiments showing a higher efficacy of this strategy in tumor destruction in comparison with CDC20siRNA‐loaded control nontargeted liposomes. These findings indicated that co‐delivery of siRNA and chemotherapeutic drugs by NACA nano‐liposomes would be a good therapeutic option worthy of further consideration to improve NB treatment (Figure 3; Bhunia et al, 2017). Another example of encapsulating siRNAs has been shown in another study that aimed to encapsulate MYCN siRNA in a liposome coated with folate molecules.…”
Section: Nanocarriers Used In Drug Deliverymentioning
confidence: 92%
“…However, the sensitivity of siRNA to RNase is a big problem that could be solved by encapsulating the siRNA in nanometric liposomes. As a result, scientists decided to design liposomes which protect siRNAs from destruction (Bhunia, Radha, & Chaudhuri, 2017; Zhu et al, 2013). Cell division cycle homolog 20 (CDC20), a protein with an important role in mitosis regulation in the cell cycle, is overexpressed in many types of cancers.…”
Section: Nanocarriers Used In Drug Deliverymentioning
confidence: 99%